Implementasi Metode Load Balancing Untuk Optimalisasi Performa Server Pada Jaringan Internet - Hamid Wijaya; Iim Abdurrohim; Jentot Tugiyono; Rhaishudin Jafar Rumandan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The increasing number of internet users and the fact that each user has various needs result in very high and fluctuating internet traffic, which has an impact on the increasing workload on servers and network infrastructure. Due to the large workload experienced by the server, an approach is needed that can distribute the workload evenly among several resources, or what is known as a load balancing technique. Thus, the main objective of this research is to optimize internet network performance by implementing load balancing techniques and measuring the performance improvements that can be achieved. Load balancing methods are used to avoid imbalances that can cause one resource to be overburdened while others may not be used optimally. For testing, connections were made 1000 times with 100 requests/second, then increased gradually up to 11,000 connections with 1100 requests/second. Test results show that at low to medium connection levels (1000/100 to 6000/600), servers without load balancing tend to provide better response times. However, as connection rates increase (from 7000/700 to 11000/1100), servers with load balancing show superiority by having better response times than servers without the technique. Therefore, this research suggests that implementing a load balancing strategy is very important for maintaining optimal performance and system stability under high workload conditions.